2D triangular anti-trichiral structures and auxetic stents with symmetric shrinkage behavior and high energy absorption. (March 2020) - Hamzehei, Ramin; Rezaei, Saeed; Kadkhodapour, Javad; Anaraki, Ali Pourkamali; Mahmoudi, Alireza
Highlights: In this research, 2D triangular anti-trichiral structure and auxetic stents with the aims of uniform shrinkage behavior and high energy absorption were introduced. Under compression, the deformation mechanisms were based on the rotation of the triangles and bending of the ligaments. In the 2D structures, the most negative Poisson's ratio values, with the values of υ y z = −0.55 and υ z y = −1.6, were measured in the structure in which the triangle edge lengths were considered 13 mm. In the cylindrical stents, the most negative Poisson's ratio values, with the values of υ z x = −2.2 and υ z y = −2.19, and uniform shrinkage behavior were observed in the stent in which the triangle edge lengths were considered 15 mm. The energy absorption capability in the triangular anti-trichiral stent was three times as high as the conventional anti-trichiral stent. The lateral displacements of the triangular anti-trichiral stent, under compression, were twice as high as the conventional anti-trichiral stent. Abstract: In this study, 2D triangular anti-trichiral structures and auxetic stents, under compression, were introduced. The cores of the anti-trichiral structures were the equilateral triangles. The deformation mechanisms in 2D structures were based on the rotation of the triangles and bending of the ligaments. A parametric study was carried out to investigate the dependence of the Poisson's ratio to the triangle edge lengths. The most auxeticity, with the values of υ y z = −0.55 and υ z y = −1.6, was obtained in the structure in which the triangle edge lengths were considered 13 mm. Next, the auxetic stents with the aims of uniform shrinkage behaviors as well as high energy absorption were introduced. For this purpose, the equilateral triangles were distributed on the cylindrical surfaces along with the peripheral and longitudinal directions. Under compression, the stent with 15mm triangle edge lengths possessed uniform shrinkage behavior, and the values of Poisson's ratio were measured υ z x = −2.2 and υ z y = −2.19. Finally, the comparisons between triangular and conventional anti-trichiral stents were performed. It was observed that the lateral displacements, as well as energy absorption of the triangular stents were twice and three times as high as the conventional anti-trichiral stents respectively. Graphical abstract: Image, graphical abstract